Technology Application of Biopore for Reduce Run Off at SDN 2 Sungai Besar Banjarbaru - Nova Annisa; Chairul Abdi; Mahmud Mahmud; Gusti Ihda Mazaya; Hafiizh Prasetia (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2021)
Biopores are holes in the soil formed as a result of organism activity to increase water absorption, reduce the risk of runoff, and preserve the environment. Making biopore infiltration holes is advantageous because it is practical, economical, and environmentally friendly. This community service activity aims to provide educational counseling and technical training to civitas of SDN 2 Sungai Besar Banjarbaru through the installation of biopore infiltration holes to prevent and overcome run off particularly during the rainy season. This community service activity follows a three-stage methodology: survey and observation, socialization and technical training, and practice creating biopore infiltration holes. Based on the outcomes of the activities, participation and collaboration with the residents went well and cooperatively, and the application of biopore infiltration holes was made in two locations throughout the garden. Thus, this community service activity benefited and was shared with the civitas of SDN 2 Sungai Besar Banjarbaru, particularly in terms of knowledge and skill transfer through the creation of biopore infiltration holes to prevent and overcome run off independently and sustainably.